Antibiotic Susceptibility Profile of Carbapenem-Resistant Klebsiella pneumoniae Isolates after Exposure to Non-Thermal Plasma - Hamza, Sanaa A.; Mohammed, Raghad S.; Al Marjani, Mohammed F.; Bekhit, Mounir M. (Al-Mustansiriyah Journal of Science, 2025)
Background: Carbapenem-resistant Klebsiella pneumoniae (CRKP) should be considered an emerging clinical threat. Because these isolates are resistant to nearly all commonly used antibiotics, control of their spread is important. Objective: This study aimed to examine the impact of non-thermal plasma on the CRKP isolates from Iraqi patients. Methods: A total of 150 specimens were collected from different clinical sources. Thirty isolates of K. pneumoniae were obtained in this study. The antibiotic susceptibility testing was conducted using Kirby-Bauer’s disk diffusion method before exposing the isolates to non-thermal plasma for 15, 30, 60, 90, and 120 seconds at a temperature of 37 °C for 24 hours. Results: The results of the study suggested that K. pneumoniae isolates exhibited differential antibiotic susceptibility following treatment with a nonthermal plasma. Both piperacillin, ceftazidime, and imipenem demonstrated increased efficacy 15 seconds after exposure with an inhibition rate of 100%, while ciprofloxacin and gentamicin showed optimal efficacy with inhibition rates of 97% and 90%, respectively. However, amikacin displayed resistant phenotypes at 15 seconds with an inhibition rate of 87%, and the inhibition rate with tetracycline and cefepime was the same at 83%; as for the time of 30 seconds and above, all nine tested antibiotics showed an inhibition rate of 100%. Conclusions: The results demonstrate the important impact of nonthermal plasma on the antibiotic susceptibility profiles of K. pneumoniae isolates. Understanding the role of nonthermal plasma in antibiotic resistance can help in developing more effective strategies for controlling infections caused by multi-resistant organisms. Further research is needed to clarify the underlying processes and their implications for treatment.